ORGANIZING AN EDUCATIONAL EXCURSION TO DEVELOP PRIMARY SCHOOL STUDENTS’ UNDERSTANDING OF ENVIRONMENTAL PROTECTION AND THE WORLDVIEW (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2025)
Organizing educational excursions fosters primary school students’ understanding of environmental protection and broadens their worldview. Through direct interaction with nature, visits to conservation sites, and guided activities, students learn sustainability principles, biodiversity, and human impact on ecosystems. These experiences cultivate responsibility, critical thinking, and global awareness essential for future environmental stewardship.